- Pengembangan Wawasan Kewirausahaan Berbasis Halal Knowledge di Desa Belapunranga Kec. Parangloe Kab. Gowa Provinsi Sulawesi Selatan: - - Nusran, Muhammad; Lantara, Dirgahayu; Muchlis, Nurmiati; Faisal AR Pelu, Muhammad (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
One of the main references for consumers in making requests for goods and services is to pay close attention to the halal label. In fact, only about 86% of MSME products in Indonesia are registered with halal certificates. Islamic boarding schools should be a place to socialize the importance of halal certification, as well as encourage entrepreneurship for students and the surrounding community. This, in fact, has not been in line with expectations, especially in remote areas. Educators do not yet have adequate scientific knowledge regarding halal certification procedures, as well as entrepreneurship. On the one hand, boarding school administrators are still required to meet operational costs to develop pesantren. On the other hand, many of the surrounding communities still have low socioeconomic status coupled with low education. This Community Partnership Program aims to solve problems in a comprehensive and sustainable manner through efforts to increase awareness and an entrepreneurial ethos based on